Legal antinomies: doctrinal and jurisprudential analysis (Revista do Tribunal Regional Federal da 3ª Região, 2024)
Law must originate from the solid foundations of social experiences, forming a preordained system, harmonious with each other and capable of responding to the demands of the established Law; as well as being flexible enough to adapt to social and technological evolution, in a protective way for future generations, in which new rights emerge all the time, putting the past in conflict with the present. In this direction, constitutional axiology frames the construction of norms that seek legal validity in their principles. A path that is often tortuous and repeatedly tested, which is not free from confrontations. The conflicts of norms called antinomies are evident, and doctrine and jurisprudence make tireless efforts to establish criteria for resolving first and second degree conflicts, apparent or real. It should not be forgotten that there are solutions already consolidated in interpretation techniques, configuring a general rule for resolving the antinomy using chronological, specialty and hierarchical criteria. However, the application of these rules often does not cover all responses. Thus, it is evident that the necessary renewal has been taking place through the rule of weighting between principles, applied today in a broader sense to all standards, including in new proposals created from the consolidation of the theory of source dialogue, which represents a new look towards harmonizing the Brazilian legal system. A hypothetical-deductive methodology and bibliographic review were used.
Keywords: Constitution; norms; harmony; conflicts; antinomies; criteria; weighting; dialogue of sources; doctrine; jurisprudence